2018
DOI: 10.1021/acs.iecr.8b01969
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Structural Modifications of Hyperbranched Polymers and Their Applications

Abstract: Hyperbranched polymers (HPs) are a subclass of dendritic polymers, having globular and highly branched structure, containing a number of functional groups emerging from a core. The core contains more than two functional sites where the growing branches are connected, resulting in the formation of a 3D macromolecule comprising a large number of peripheral groups. Their versatile properties and facile structural modifications have attracted considerable attention of researchers. HPs have been used in various app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 239 publications
0
44
0
Order By: Relevance
“…3. However, such units may be favoured over others depending on the polymer synthesis method 19,20 . Propylene Carbonate is classified as AB 1 -type monomer, since it has only one OH active site to polymerize.…”
Section: Hyperbranched and Highly Branched Unitsmentioning
confidence: 99%
“…3. However, such units may be favoured over others depending on the polymer synthesis method 19,20 . Propylene Carbonate is classified as AB 1 -type monomer, since it has only one OH active site to polymerize.…”
Section: Hyperbranched and Highly Branched Unitsmentioning
confidence: 99%
“…Furthermore, the high density of functional groups at the periphery of HBPs can be exploited to introduce functionalities on HBPs. [39] For biomedical applications, effective contrast agent probes for magnetic resonance imaging or targeting groups to promote the specific accumulation of drug carriers at the target site also known as targeted drug delivery have been considered. In this review, we propose to provide a comprehensive overview of the different types of targeting ligands used for targeted drug delivery and the strategies used to afford these HBP-based nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…HB polymers have been used in various fields of technologies such as biological applications (therapeutic, protein delivery, antimicrobial, etc. ), coatings, catalysis, nanotechnology, additives, sensors (chemical and bio), energy storage applications (thermal energy storage, rechargeable batteries, and solar cells) and electroluminescence applications …”
Section: Introductionmentioning
confidence: 99%
“…), coatings, catalysis, nanotechnology, additives, sensors (chemical and bio), energy storage applications (thermal energy storage, rechargeable batteries, and solar cells) and electroluminescence applications. 9,24 Recently, our group focused on the use of highly basic and as well as a nucleophilic catalyst, 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) in the extremely rapid synthesis of polythioethers and the postfunctionalization of unsaturated polyester backbones. [25][26][27] More recently, we showed that dimethyl acetylenedicarboxylate (DMADC) and various dithiols could be polymerized in the presence of TBD to give a series of linear polythioethers.…”
mentioning
confidence: 99%